2012
DOI: 10.1111/j.1463-5224.2012.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methicillin‐resistant Staphylococcus aureus (MRSA) in the microbial flora from the conjunctiva of healthy donkeys from Sicily (Italy)

Abstract: This study contributes to the knowledge about normal ocular flora and MRSA occurrence in donkey farms in Sicily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…Several studies have reported the emergence of MRSA among farm animals [4-7]. Moreover, the emergence of MRSA in the equine population has been demonstrated [8-10] and, very recently, MRSA isolates have been detected in microbiota of healthy donkeys [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the emergence of MRSA among farm animals [4-7]. Moreover, the emergence of MRSA in the equine population has been demonstrated [8-10] and, very recently, MRSA isolates have been detected in microbiota of healthy donkeys [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance has been an increasing problem worldwide, especially in nosocomial infections . Recently, methicillin‐resistant Staphylococcus aureus (MRSA) was found on the ocular surfaces of healthy donkeys in Italy . Dogs that visited human health‐care facilities were at risk of acquiring MRSA, particularly when they licked patients or accepted treats during visits .…”
Section: Discussionmentioning
confidence: 57%
“…The most frequently recovered bacteria in the current study were Staphylococcus, which are commonly found on the normal conjunctiva of most domestic animals . However, they are opportunistic pathogens and the most frequently isolated organisms in cases of canine bacterial conjunctivitis .…”
Section: Discussionmentioning
confidence: 66%
“…However, they are opportunistic pathogens and the most frequently isolated organisms in cases of canine bacterial conjunctivitis . Recently, methicillin‐resistant Staphylococcus aureus has been isolated from the healthy conjunctival sac of dogs and donkeys …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation